Beyond iBeer - exploring the potential of smartphone sensors for performance diagnostics in sports - Hummel, O.; Fehr, U.; Ferger, K. (International Journal of Computer Science in Sport, 2013)
In recent years, modern technology significantly improved the possibilities for performance diagnostics in sports. However, the technical equipment used for this purpose is usually still complicated to transport, to set-up as well as to operate and to top it all rather expensive. Off-the-Shelf smartphones on the other hand are relatively cheap, independent of power outlets and familiar to a large range of users. As smartphones nowadays contain sophisticated sensor technology, it seems promising to investigate their potential to cheapen performance diagnostics in sports and thereby make it available to a larger target audience. This article presents the results of an explorative study that demonstrate how a current Android-based smartphone is able to deliver results in the analysis of "bouncing" jumps that are comparable to common force-platforms. Hence it seems worthwhile to create an app able to deliver this service automatically on mobile devices in the near future